Implementasi Nilai Islamisasi Ilmu Dalam Membendung Arus Westernisasi - Tonny Ilham Prayogo (EL-FIKR: Jurnal Aqidah dan Filsafat Islam, 2023)
Islamization of science is an effort to integrate Islamic principles, values, and views into various fields of science and education. This effort is also a prevention of the spread of Westernization in education, culture and morals. Westernization refers to the influence of the culture or lifestyle of western countries on other societies or nations outside the western region. With the swift flow of technology, the westrenization element enters and hegemonizes the area outside of it until the human population in the world often follows it. The purpose of this research is to reveal and present Islamic sciences from various fields that have been contaminated with western culture. The method used is descriptive analysis where the data obtained is then described and explained with a series of sentences with actual conditions. The results of this study indicate that the importance of Islamization in stemming the current of wetrenisation that has affected aspects of life, especially in the fields of science and education.